Dancing with Jesus as the incarnate male 'missionary' conversant: A homeless group's reading of John 4 in dealing with gender-based violence - Baron, Eugene (Verbum et ecclesia, 2019)
In this article, the metaphor of dancing is used to discuss the skewed gender relations in society as a result of the various interpretations available in terms of the narrative of Jesus and the Samaritan woman (Jn 4). The question explored is the following: how scholarly interpreters of the Bible and the homeless people describe this 'dancing', that is, the human movements between the male and female conversation partners? The author uses the 'woman-friendly' interpretations of various theologians on the John 4:1-42 narrative and juxtaposes it against other theologians' interpretations. Furthermore, the author discusses how a homeless group in the City of Tshwane reflects on and interprets the text. The article builds on the premise that biblical texts like John 4:1-42 - which are interpreted in a way that sustains patriarchy - serve as the cause for gender-based violence. Therefore, although the article does not refer directly to the issue of gender-based violence, it is contributing to 'woman-friendly' interpretations of Biblical texts to counter patriarchal tendencies in society.Intradisciplinary and/or interdisciplinary implications: This is interdisciplinary study as it integrates gender-based violence in the field of sociology, public theology, feminist ethics with missiology. It is also integrating the field of biblical hermeneutics with missiology in terms of a specific biblical text namely Jn. 4 that is analysed.